Comparison of Efficacy and Safety of Lispro and Aspart Evaluated by Continuous Glucose Monitoring System in Patients with Newly Diagnosed Type 2 Diabetes - Bing-li Liu; Guo-ping Yin; Feng-fei Li; Yun Hu; Jin-dan Wu; Mao-yuan Chen; Lei Ye; Xiao-fei Su; Jian-hua Ma (International Journal of Endocrinology)
Objective. To compare the effect of the rapid-acting insulin analogues (RAIAs) aspart (NovoRapid) and lispro (Prandilin) on glycemic variations by continuous glucose monitoring system (CGMS) in patients within newly diagnosed type 2 diabetes mellitus (T2DM) receiving continuous subcutaneous insulin infusion (CSII) and metformin intensive therapy. Methods. This is a single-blind randomized controlled trial. A total of 110 patients with newly diagnosed T2DM and with hemoglobin A1c (HbA1c%) above 9% was hospitalized and randomly divided into two groups: group Asp (NovoRapid group) and group Lis (Prandilin group). They all received CSII and metformin therapy. Treatments were maintained for 2-3 weeks after the glycaemic target was reached. C-peptide and insulin and fructosamine were determined. CGMS was continuously applied for 4 days after reaching the glycemic target. Results. There were no significant differences in daily dosages of insulin, fasting plasma C-P and 2 h postprandial C-P and insulin, and fructosamine at the baseline and endpoint between the groups Asp and Lis. No significant differences were seen in the 24 h mean amplitude of glycemic excursions (MAGE), 24 h mean blood glucose (MBG), the standard deviation of the MBG (SDBG), fasting blood glucose, number of glycemic excursion (NGE), and the incidence of hypoglycemia between the two groups. Similarly, no significant differences were found in areas under the curve (AUC) of glucose above 10.0 mmol/L or the decremental area over the curve (AOC) of glucose below 3.9 mmol/L between the two groups. Conclusions. Lispro and aspart had the similar ability to control the glycemic variations in patients with newly diagnosed T2DM. This study was registered with ClinicalTrials.gov, number ChiCTR-IPR-17010338.